Geotechnical earthquake engineering - Kramer, Steven Lawrence (Prentice-Hall international series in civil engineering and engineering mechanics, 2014)
This is the first book on the market focusing specifically on the topic of geotechnical earthquake engineering. Also covers fundamental concepts in seismology, geotechnical engineering, and structural engineering.